2021
DOI: 10.1145/3448107
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Collaborative-Filtering for Personalized Behavior Modeling

Abstract: The prevalence of mobile phones and wearable devices enables the passive capturing and modeling of human behavior at an unprecedented resolution and scale. Past research has demonstrated the capability of mobile sensing to model aspects of physical health, mental health, education, and work performance, etc. However, most of the algorithms and models proposed in previous work follow a one-size-fits-all (i.e., population modeling) approach that looks for common behaviors amongst all users, disregarding the fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 39 publications
1
30
0
Order By: Relevance
“…The PHQ-9 is an evaluative questionnaire used to assess depression severity. The PHQ-9 has been used effectively in multiple studies related to depression [ 38 , 39 ]. The questionnaire consists of a set of 9 questions with scores between 0 and 3.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The PHQ-9 is an evaluative questionnaire used to assess depression severity. The PHQ-9 has been used effectively in multiple studies related to depression [ 38 , 39 ]. The questionnaire consists of a set of 9 questions with scores between 0 and 3.…”
Section: Methodsmentioning
confidence: 99%
“…Mobile sensing-based mental health studies have been conducted in the areas of bipolar disorder [27], schizophrenia [28], anxiety [29,30], stress [31,32], and depression [33][34][35][36][37][38][39]. These studies have shown that mobile sensing can play an integral role in detecting and predicting mental health-related problems.…”
Section: Mobile Sensing In Mental Health Appsmentioning
confidence: 99%
See 2 more Smart Citations
“…We computed features from the 6 sensors of calls, heart rate, location, screen, sleep, and steps, given their potential to inform depressive symptoms [29,[44][45][46][47][48], as well as fatigue [49], MS symptom burden such as decreased mobility [27], and sleep quality [50,51].…”
Section: Feature Extractionmentioning
confidence: 99%